PENGARUH TINGKAT RELIGIUSITAS, PENGETAHUAN, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP PREFERENSI MENABUNG MAHASISWA UNIVERSITAS MUHAMMADIYAH PALEMBANG PADA BANK SYARIAH - Hasanah, Fadhilatul (Universitas Muhammadiyah Palembang, 2019)
Islamic Bank is a financial institution that functions as a fund collector and distributed it to the community, so that the activity of raising funds (saving) was the most important thing for banks and customers. Students who were a potential segmentation for saving activities (raising funds) had a variety of savings preferences. The purpose of this study was to analyze the influence of students partially and simultaneously on the level of religiosity, knowledge, product quality and service quality to saving preferences of University Muhammadiyah Palembang's students in Islamic Banks. The method of this study was quantitative descriptive with multiple linear regression analysis techniques. The study population was University Muhammadiyah Palembang's students with 99 respondents. The results of this study showed partially the value of t count>t table (9.602>1.985) and the value of sig t <0.05 (0.000<0.05) so that the level of religiosity influenced the saving preferences of University Muhammadiyah Palembang's students in Islamic banks that were the form of religious obedience because students used Islamic banks were related to the issue of faith and confidence in the prohibition of usury for Muslims but partially there is no influence of knowledge, product quality and service quality to saving the preferences of University Muhammadiyah Palembang's students in Islamic Banks, while simultaneously showed the value of Fcount>Ftable (24,471>2,470) and sig F value <0.05 (0,000<0,05) so that the level of religiosity, knowledge, product quality and service quality to saving the preferences of University Muhammadiyah Palembang's students in Islamic Banks.